Effectiveness and tolerability of focal versus radial extracorporeal shock wave therapy in patients affected by plantar fascia enthesopathy - Edoardo Pisani; Claudio Curci; Antimo Moretti; Anna Mazzola; Marco Paoletta; Sara Liguori; Giovanni Iolascon (Verduci Editore, 2020)
Plantar fascia enthesopathy is the most common cause of heel pain. Extracorporeal shock wave therapy (ESWT) is widely used in patients affected by this condition. The aim of this study was to compare efficacy and tolerability of ESWT modalities in the treatment of plantar fasciitis. We included 42 patients receiving 1 session of focused ESWT (f-ESWT group) or radial ESWT (r-ESWT group) per week for 3 weeks. Pain assessment was performed at baseline, before each session, and 1 month after the last session using brief pain inventory (BPI) severity index, and interference index (II). Tolerability was defined in terms of patient discomfort after treatment assessed by numeric rating scale at baseline and after each session. Plantar fascia changes in ultrasonography were further investigated. A significant reduction of BPI-II (P<0.001) was reported in both groups, although no between-group differences were found. Plantar fascia thickness showed significant reduction only in the f- ESWT group (P=0.028). Patient's tolerability was significantly better in the r-ESWT group (P<0.05). Our study confirms that ESWT is effective for reducing pain and disability in patients affected by plantar fasciitis, although r- ESWT seems to be better tolerated.